Problematika kontinence po hlubokých pánevních anastomózách pri Ca recti - Michek, J; Sutorý, M; Zelnícek, P; Kubacák, J (Acta medica (Hradec Kralove). Supplementum, 1997)
Based on the complex evaluation of the continence by anorectal manometry, EMG examination of sphincters, transrectal sonography, defecography and Colonic Transit Time examination, the analysis of the group of 15 patients partially incontinent after operation of carcinoma of the lower part of the rectum has been done. In these patients the deep pelvic anastomosis or coloanal anastomosis was performed. In none of the patients any serious organic damage of sphincters was manifested, the causes were dominantly extrasphincteric and functional, solvable well by conservative methods.
Keywords: fekální inkontinence; anastomóza chirurgická; Fecal Incontinence; Rectal Neoplasms; nádory rekta; Anastomosis, Surgical; Humans; Intestines; Postoperative Complications; pooperační komplikace; lidé; střeva